English Students’ Vocabulary Size and Level at a Private University in West Java, Indonesia - Fenty Lidya Siregar (Bina Nusantara University, 2020)
The research investigated the EFL (English as a Foreign Language) undergraduate students’ vocabulary knowledge (size and level). The research involved 40 second-semester students who were enrolling in two reading courses at an English Department in a private university in West Java, Indonesia. Vocabulary Size Test by Nation and Beglar; and Vocabulary Level Test by Webb, Sasao, and Ballance were used to gain data. It is found that the participants’ average vocabulary size is 8.732,5 word-families. The finding of the research also reveals that only ten students master 1.000-5.000 word-levels. It means that despite a big vocabulary size that many students have, 75% of them only know a limited high and mid-frequency vocabulary. The findings imply that the students still need to read graded readers to master high and mid-frequency levels. The current research project also indicates that the students might have met more low-frequency words than high and mid-frequency words in their language learning prior to their current extensive reading program.